2003
DOI: 10.1016/s0165-1765(03)00218-0
|View full text |Cite
|
Sign up to set email alerts
|

Inada conditions imply that production function must be asymptotically Cobb–Douglas

Abstract: We show that every twice-continuously differentiable and strictly concave function f : R + → R + can be bracketed between two C.E.S. functions at each open interval. In particular, for the Inada conditions to hold, a production function must be asymptotically Cobb-Douglas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…Inada included the following conditions: the function is continuously differentiable; the function is concave, that is, the derivative of the function is decreasing; the limit of the derivative towards 0 is positive infinity; and the function is increasing in x. Barelli and deAbreu Pessôa (2003) showed that for the Inada conditions to hold, the elasticity of substitution is asymptotically equal to 1. However, the Inada conditions only apply fully if the Cobb-Douglas production function is the appropriate function in congruence with the empirical facts.…”
Section: Control Variablesmentioning
confidence: 99%
“…Inada included the following conditions: the function is continuously differentiable; the function is concave, that is, the derivative of the function is decreasing; the limit of the derivative towards 0 is positive infinity; and the function is increasing in x. Barelli and deAbreu Pessôa (2003) showed that for the Inada conditions to hold, the elasticity of substitution is asymptotically equal to 1. However, the Inada conditions only apply fully if the Cobb-Douglas production function is the appropriate function in congruence with the empirical facts.…”
Section: Control Variablesmentioning
confidence: 99%
“…However, in general, CES functions other than the Cobb-Douglas function do not satisfy the Inada conditions (Barelli and de Abreu Pessoa, 2003). It is possible for extreme parameter values -low savings rate, high depreciation rates, high levels of β and low levels of σ -that (8) is not met neither near the origin nor for any positive value of K so that there is no positive equilibrium level of capital.…”
Section: Steady-state and Comparative Staticsmentioning
confidence: 99%
“…Identification of the wedges is quite intuitive. The international wedge, for example, is determined by differences in consumption growth rates across countries from equation (3). Likewise, the capital wedge is identified by differences in estimated marginal products of capital (from capital/output ratios) from growth rates of consumption within a country (2), and the labor wedge is determined from a comparison of hours worked and consumption levels within a country (1).…”
Section: Remarks On Open Economy Business Cycle Accountingmentioning
confidence: 99%
“…Note that the competitive equilibrium's international wedge (see Figure7) corresponds to the growth rate of the pseudo planners wedge or what we call cumulative international wedge (see Figure 6). 3 Since all wedges are relative to the rest of the world, there are only two lines in these Figures.…”
Section: International Wedgesmentioning
confidence: 99%